Functionalized macrocyclic molecule as well as preparation method and application thereof - JIANG WEI; YANG XIRAN (2023)
The invention discloses a functionalized macrocyclic molecule as well as a preparation method and application thereof. The structure of the functionalized macrocyclic molecule is shown as a general formula I or II, R1 and R2 are different, R1 is independently selected from alkyl, naphthenic base and aromatic hydrocarbon when appearing every time, and alkyl is selected from linear alkyl with 1-16 C atoms or branched alkyl with 3-16 C atoms; the cycloalkyl is selected from cycloalkyl with 3 to 16 C atoms; each occurrence of R2 is independently selected from a linear alkyl group, H, or an inorganic cation wherein the linear alkyl group is selected from a linear alkyl group having 1 to 16 C atoms. The functionalized macrocyclic molecule has a fluorescent property, can detect a substance to be detected according to the change of fluorescence, has excellent subject-object recognition property, can be bonded with polar micromolecules such as toluene and p-xylene in a mixed solvent of water and an organic solvent, ca